2018
DOI: 10.1038/s41598-018-19205-4
|View full text |Cite
|
Sign up to set email alerts
|

The GluN2A Subunit Regulates Neuronal NMDA receptor-Induced Microglia-Neuron Physical Interactions

Abstract: Microglia are known to engage in physical interactions with neurons. However, our understanding of the detailed mechanistic regulation of microglia-neuron interactions is incomplete. Here, using high resolution two photon imaging, we investigated the regulation of NMDA receptor-induced microglia-neuron physical interactions. We found that the GluN2A inhibitor NVPAAM007, but not the GluN2B inhibitor ifenprodil, blocked the occurrence of these interactions. Consistent with the well-known developmental regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…This discrepancy may be due to the differential response of microglia in CA1 (Avignone et al, ) versus CA3 (our investigation) regions of the hippocampus after KA‐induced seizures. Consistently, we noted regional difference of microglial response to NMDA‐induced neuronal hyperactivities in mouse hippocampus (Eyo et al, ). In addition, we noted an increase in expression of P2Y12 in the CA1, whereas the expression was downregulated in the CA3 after KA induced seizures (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to the differential response of microglia in CA1 (Avignone et al, ) versus CA3 (our investigation) regions of the hippocampus after KA‐induced seizures. Consistently, we noted regional difference of microglial response to NMDA‐induced neuronal hyperactivities in mouse hippocampus (Eyo et al, ). In addition, we noted an increase in expression of P2Y12 in the CA1, whereas the expression was downregulated in the CA3 after KA induced seizures (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a different phenomenon (where microglial processes converged focally to dendritic hotspots, rather than radiating outward on neuronal dendrites) was discovered following global glutamatergic activation or kainic acid induced seizures [16]. Both phenomena depend specifically on the GluN2a NMDAR subunit [13]. Knocking out P2Y12Rs abolished both phenomena and corresponded with increased seizure intensities [16,17] suggesting that these interactions may serve to downregulate neuronal activity.…”
Section: Transient Interactions 21 Engaging Synaptic Elements: Dendrmentioning
confidence: 99%
“…In a narrow window between P8 and P10, microglia frequently induced filopodia, precursors to spines, on dendritic shafts in a contact-dependent manner. Moreover, microglial depletion correlated with reduced spine densities and reduced functional synapses suggesting that microglia promote synaptogenesis in the developing cortex [13]. Interestingly, microglia promote learning-dependent synapse formation in adults in a brain derived neurotrophic factor (BDNF)-dependent manner [43].…”
Section: Transient Interactions 21 Engaging Synaptic Elements: Dendrmentioning
confidence: 99%
“…Whole-cell patch clamp experiments have demonstrated that the activation of dendritic NMDA receptors in a single neuron is enough to trigger the growth of microglial extensions, establishing a direct link between neuronal activity and microglial dynamics. In relation to the mechanisms involved in this physical interaction, mediated by electrical activity between microglia and neurons, it has been established that this regulation is mediated by the GluN2A subunit of the NMDA receptor [20]. Besides that, microglia shift from different stages of activation also depends on a cross-talk between neurons, astrocytes, and microglial cells, which is essential for adaptive neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%